Remitting neuropsychiatric symptoms in COVID‐19 patients: Viral cause or drug effect?. Issue 3 (19th November 2021) - Forero‐Peña, David A.; Hernandez, Matthew M.; Mozo Herrera, Iriana Paola; Collado Espinal, Iván Bolívar; Páez Paz, Joselyn; Ferro, Carlos; Flora‐Noda, David M.; Maricuto, Andrea L.; Velásquez, Viledy L.; Camejo‐Avila, Natasha A.; Sordillo, Emilia M.; Delgado‐Noguera, Lourdes A.; et al.
Abstract: Numerous reports of neuropsychiatric symptoms highlighted the pathologic potential of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and its relationship the onset and/or exacerbation of mental disease. However, coronavirus disease 2019 (COVID‐19) treatments, themselves, must be considered as potential catalysts for new‐onset neuropsychiatric symptoms in COVID‐19 patients. To date, immediate and long‐term neuropsychiatric complications following SARS‐CoV‐2 infection are currently unknown. Here we report on five patients with SARS‐CoV‐2 infection with possible associated neuropsychiatric involvement, following them clinically until resolution of their symptoms. We will also discuss the contributory roles of chloroquine and dexamethasone in these neuropsychiatric presentations. Highlights: SARS‐CoV‐2 Infection and COVID‐19 treatments have a potential catalytic role on neuropsychiatric complications. Cytokine storm and exacerbated cytotoxicity could be implicated in COVID‐19 related neuropsychiatric symptoms. The use of corticosteroids must be considered balancing risk/benefit to the patient.